Kecerdasan Logis Matematis Siswa dalam Menyelesaikan Soal Matematika Kelas IX SMP - Mulyana, Jujun; Hakim, Dori Lukman (Universitas Muria Kudus, 2023)
The aim of the present study was to portray students' mathematical logical intelligence in class VIII at one of the junior high school in Karawang Regency. Mathematical logical intelligence is a skill that can help students solve math problems. Students' inability to calculate and use reasoning is still a concern in learning mathematics. Skills in processing words and numbers, utilize reasoning, analyzing problems logically, finding formulas and conducting scientific investigations are intelligence that students must have. The research used descriptive qualitative approach. The subjects in this article are 3 students out of 40 students taken randomly purposive sampling of the criteria of high, medium, and low levels of logical-mathematical intelligence based on the results of the selected tests to observe and analyze logical-mathematical abilities. The instrument used in this study was a logical mathematical intelligence test instrument tailored to indicators of mathematical logical intelligence, namely: 1) ability to process numbers and solve calculations problems, 2) ability to use mathematical analysis, and 3) ability to solve problems using thinking skills, 4) ability to solve math problem related to patterns and relationships, and 5) ability in inductive and deductive thinking. The results showed that the average ability of students' logical-mathematical intelligence was still in the moderate category